Suffering and moral responsibility - Mayerfeld, Jamie (Oxford ethics series., 1999)
"In this original study, Jamie Mayerfeld undertakes a careful inquiry into the meaning and moral significance of suffering. Understanding suffering in hedonistic terms as an affliction of feeling, he addresses difficulties associated with its identification and measurement. He then turns to an examination of the duty to relieve suffering: its content, its weight relative to other moral considerations, and the role it should play in our lives."--Jacket